Optimization Of Sistem Manajemen Kinerja For Improved Investigator Outcomes In The Indonesian National Police - Alfamantar, Egidio Fernando; Fadillah, Muhammad Alif (Jurnal Ilmu Kepolisian, 2025)
This study investigates the effectiveness of the Sistem Manajemen Kinerja (SMK) in enhancing investigator performance to uphold Polri Presisi values within the Karawang Resort Police. Polri Presisi emphasizes predictive, responsible, and transparently equitable policing, essential for maintaining public trust and operational integrity. Recent incidents of police-involved violence and unprofessional conduct underscore critical challenges in aligning police practices with Presisi ideals. Employing a descriptive analysis approach utilizing data from 2022 to 2024 at Karawang Resort Police, the study reveals significant gaps in Sistem Manajemen Kinerja utilization, including inadequate socialization, mentorship challenges amidst heavy workloads, and underutilization of evaluations for personnel development. Recommendations focus on forging collaborative training partnerships with academic institutions, international training for supervisors, and enhancing information technology to bolster investigative capabilities. Implementing these recommendations aims to elevate investigator performance and overall operational effectiveness at the Karawang Resort Police, which is crucial in navigating contemporary policing challenges while adhering to Polri Presisi standards in the dynamic landscape of Industry 4.0.